Implementing identity management on AWS : a real-world guide to solving customer and workforce IAM challenges in your AWS cloud environments /: a real-world guide to solving customer and workforce IAM challenges in your AWS cloud environments. (2021) - Lehtinen, Jon; Hutchinson, Steve
No abstract available